Penggunaan Pendekatan Science, Teknology, Eingineering And Mathematics (STEM) Untuk Meningkatkan Kemampuan Kognitif Peserta Didik, Kelas XI SMA IT Fagogoru Kabupaten Halmahera Tengah Pada Konsep Panel Surya - Manaf, Firja; Ismail, Susi (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2024)
The variables in this research are: (1) Use of a STEM approach, (2) Increasing students' cognitive abilities. This research includes classroom action research (PTK), the problem formulation is whether using the STEM learning model can improve students' abilities in using the Science, Technology, Engineering, and Mathematics (STEM) approach for Class XI SMA IT Fagogoru, Central Halmahera Regency on the Solar Panel Concept? . The aim of this research is: to determine the cognitive abilities of class IX students at SMAS IT Fagogoru, Central Halmahera Regency. The instruments used in this research were observation and essay test sheets. The results of this research use the application of the STEM Approach method to improve the cognitive abilities of students in class IX SMAS IT Fagogoru, Central Halmahera Regency, without increasing the cognitive abilities of students. This is characterized by students' cognitive abilities being in the high category, namely in cycle I 3 students completed it and cycle 13 students completed.